(untitled) (Research, Society and Development, 2022)
Objective: to show trends in gastric cancer mortality in the city of Cáceres and in the state of Mato Grosso, from 2010 to 2019. Methodology: ecological study, with proportional mortality and approach to study the trend of mortality rates for malignant stomach cancer in the period 2010 to 2019 in Cáceres, Mato Grosso, Brazil. Results and Discussion: Proportional mortality rates were higher in the age group from 45 to 79 years old and despite the rates having fluctuated and increasing during the study period, they were not significant (p>0.05) for the city of Cáceres. The results found coincide with other studies in the literature, which indicated the predominance of deaths from stomach cancer in males and associated this factor not only with genetics but also with lifestyle. Conclusion: The importance of expanding actions is highlighted, with an emphasis on strengthening prevention and health promotion actions, in Primary Care, to reduce morbidity and mortality, increase life expectancy and provide better quality of life for patients.